Development of Asahan River Tourism Activities in Support of National Tourism Strategic Area of Lake Toba - Mega Fitriani Adiwarna Prawira; Beta Budisetyorini; Deddy Adisudharma; Dicky Arsyul Salam; Wisi Wulandari; Eko Susanto (Journal of Tourism Sustainability, 2021)
Following up on the Development of The National Tourism Strategic Area of Lake Toba, which was directed in the study "Integrated Tourism Masterplan for Lake Toba" (ITMP Danau Toba) in 2018, one of which was the development of river-based natural tourism attractions allocated in the Asahan Watershed including Asahan Regency, Tanjung Balai Municipality, Toba Samosir Regency, and Simalungun Regency. Regarding the policy of river-based tourism attractions, this research is focused on developing river tourism activities that will have implications for the development of the natural attraction of the Asahan River. This study has produced a mixed method of sustainable tourism development strategies by prioritizing the benefits of the ecological, socio-economic and cultural environment. Development is directed towards packaging special interest tourism products following the characteristics of available resources.